High School Students’ Creative Writing Texts: Culture, Travel, Relationships, Life Incidents, and Asian Indian Epistemology - Iyengar, Dr. Kalpana Mukunda; Henkin, Dr. Roxanne.; Singh, Ms. Manaswita (IJRDO- Journal of Educational Research, 2016)
Gayathri Vidapeeth, Haridwar, India is an educational institution affiliated withDev Sanskrithi Vishwavidyalaya (DSVV), Haridwar. In the summer of 2015, a delegationfrom the University of Texas at San Antonio (department of Interdisciplinary Learningand Teaching) offered professional development to instructors and students at DSVVthrough an invitational summer institute. The institute was modeled after the San AntonioWriting Project, a site network of the National Writing Project. One of the co-directorsof the Haridwar Writing Project collected narratives from high school students atGayathri Vidyapeeth after teaching classes using the writing workshop model for a week.In this study, the director, co-director, and a Haridwar Writing Project teacher consultantcollaborated to analyze the data collected at the school. Data was analyzed utilizing fourdifferent approaches to narrative writing – Bruner’s ten features of narrative, Riessman’sthematic, and Frawley’s therapeutic and semantic scales analysis.